Aktivitas Antibakteri Ekstrak Daun Eceng Gondok (Eichhornia crassipes) Terhadap Bakteri Escherichia coli - Azzahra, Fatimah; Darsono, Putri Vidiasari; Hidayah, Nur; Mahdiyah, Dede (Universitas Borneo Lestari, 2026)
Infectious diseases are health problems that can spread from one individual to another and are dangerous if not treated. One of the bacteria that causes disease is Escherichia coli. The high rate of irrational use of antibiotics is the cause of cases of antibiotic resistance. As an alternative option, use traditional medicine from plants, namely water hyacinth (Eichhornia crassipes) which has secondary metabolite compounds that function as antibacterials. To determine the antibacterial effectiveness of water hyacinth (Eichhornia crassipes) extract in inhibiting the growth of Escherichia coli. Antibacterial activity used the well diffusion method and determination of the Minimum Inhibitory Concentration and Minimum Kill Concentration using the liquid dilution method which was analyzed statistically by the non-parametric Kruskal-Wallis Test and Mann Whitney Test. Water hyacinth extract (Eichhornia crassipes) contains secondary metabolite compounds of flavonoids, alkaloids, tannins and terpenoids showing antibacterial activity against Escherichia coli with an inhibitory zone diameter of 12.34 mm, MIC value at a concentration of 25% and does not have MBC. The results of statistical analysis show that there is a significant difference with a p value of 0.004 in Kruskal-Wallis and in Mann-Whitney it shows a p value of 0.025. Water hyacinth extract (Eichhornia crassipes) has an effect on Escherichia coli.